Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1073/pnas.0507195103
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphate modulates blood coagulation and fibrinolysis

Abstract: Inorganic polyphosphate is an abundant component of acidocalcisomes of bacteria and unicellular eukaryotes. Human platelet dense granules strongly resemble acidocalcisomes, and we recently showed that they contain substantial amounts of polyphosphate, which is secreted upon platelet activation. We now report that polyphosphate is a potent hemostatic regulator, accelerating blood clotting by activating the contact pathway and promoting the activation of factor V, which in turn results in abrogation of the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
628
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(653 citation statements)
references
References 31 publications
17
628
2
6
Order By: Relevance
“…Similar acidocalcisome compartments can be found in other single-celled eukaryotes, including trypanosomes, apicomplexans, and Dictyostelium, as well as evolutionarily distant organisms such as bacteria and humans (53). The mechanisms of polyphosphate traffic and storage may have clinical implications, as platelets release polyphosphate to stimulate blood coagulation (54,55).…”
Section: Resultsmentioning
confidence: 99%
“…Similar acidocalcisome compartments can be found in other single-celled eukaryotes, including trypanosomes, apicomplexans, and Dictyostelium, as well as evolutionarily distant organisms such as bacteria and humans (53). The mechanisms of polyphosphate traffic and storage may have clinical implications, as platelets release polyphosphate to stimulate blood coagulation (54,55).…”
Section: Resultsmentioning
confidence: 99%
“…PolyP polymers of this size are frequently found in mammalian cell signaling, and these molecules have been reported to stimulate mTOR kinase in mammary cancer cells, 39 to interact with fibroblast growth factor, 40 to be released by activated platelets, 6 and to modulate blood coagulation. 7 We have previously described that the addition of millimolar concentrations of extracellular polyP induces apoptosis specifically in MC and plasma cells. 12 However, in the present work, we studied intracellular polyP in MC.…”
Section: Discussionmentioning
confidence: 99%
“…4 Since our discovery that polyP is abundant and released by activated platelets, 6 there has been increasing interest in this polyanion in hematology. It has been found that released extracellular polyP modulates blood coagulation in vitro 7 and in vivo, 8 increases vascular permeability, 8 enhances fibrin clot structure, 9,10 promotes the inhibitory effect of factor VII activating protease on vascular smooth muscle cell proliferation, 11 and induces apoptosis in plasma cells and MC. 12 In platelets, intracellular polyP is localized principally in dense granules (which are similar to acidocalcisomes), 6 and this characteristic has been used to diagnose d-storage pool diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Besides negatively charged artificial surfaces, several 'natural' surfaces have been proposed to activate FXII in vivo, such as amyloid aggregates (Yasuhara et al, 1994;Bergamaschini et al, 1998Bergamaschini et al, , 2001), polyphosphates (Smith et al, 2006;Mü ller et al, 2009), collagen (Meijden et al, 2009) and misfolded proteins (Maas, GoversRiemslag et al, 2008). Remarkably, not all of these surfaces result in activation of both the intrinsic coagulation pathway and the kallikrein-kinin system.…”
Section: Introductionmentioning
confidence: 99%